Manifestation and response of Laryngopharygeal reflux to treatment in Kurdistan -IRAQ - .Said Mustafa Said (مجله كليه طب الكندي, 2010)
BACKGROUND: In 1972 complete description of the inflammation of posterior third of the vocal cords was done, with barium swallow confirming Gastro Esophageal Disease [CRED] & subsequent successful symptomatic treatment with antacid. The possible association between GERD & chronic laryngitis was initially known as acid laryngitis .2 *from the Department of ENT, Hawlear Medical College, Hawlear university. Department of ENT, Rezgary Teaching Hospital, Erbil. Correspondence to : Dr.Said Mustafa Said Corespondence Address to : Dr.Said Mustafa Said _ E- mail: Email elaf3d@yahoo.com Mob. 07504563829 Recived at : 15 th Dec 2009 Accepted at : 3ed Nov 2010